Awareness and Practice of Gender Equality among the College Students in a Catholic School - Lanaban, Miezy Mae; Olete, Jasmine Leonor; Baylon, Vincent; Fernando, Daniel (JPAIR Institutional Research, 2025)
This study examined the level of awareness and extent of practice of gender equality among college students in a Catholic school during the 2024-2025 academic year. Additionally, it assessed the relationship between the awareness and practice of gender equality. This study employed a quantitative research design, primarily using the descriptive-correlational approach. The respondents consisted of a stratified random sample of 242 college students. In gathering the data, a validated and reliability-tested 63-item researcher-made questionnaire was utilized. The study employed a 5-point Likert scale in both constructs. In analyzing the data, mean, standard deviation, and Spearman rank-order correlation were used. Notably, this study strictly adhered to the ethical guidelines and principles. Generally, the students demonstrated an awareness of gender equality. Additionally, the students showed a very great extent of practice of gender equality. Moreover, a significant positive relationship was found between awareness and practice, indicating that higher levels of awareness are associated with a greater extent of practice. This suggests that students who are more aware of gender equality are also more likely to practice it actively in various contexts. The findings highlight the critical role of continuously implementing effective teaching and pedagogy, particularly through the subject Gender and Society (SSP 101), in sustaining and strengthening both awareness and practice of gender equality among students.
Keywords: Awareness; Practice; Gender Equality; College Students; Catholic School; Philippines